(3OjhGf cTGLes - (3cTGLe , eMehO Hf GdMSjf Hf GdSfOj Hf TGgc, CHh GdaJM,J (B360 (3g` s ((3MdH GdeMQhSI s)
(3ChdgG (B:s
(3hQCJ CfgG JMSf HGdeUO aJGgJ s
(3BNQgG (B:s
(3Ke CJi jSYi HgG cGdegOi cCfgG bO HNQJ HGdfO BNQ eG hLOfG ef TYQ CHj GdaJM cTGLe s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B43 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B159s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
Keywords: (3GdCOHs